2020
DOI: 10.1017/dsd.2020.143
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Land, Planting First Seeds; Lead User Research in Early Stage Design for Intelligent Ecosystems

Abstract: This contribution explores the potential of lead user research for early-stage designing for intelligent ecosystems through a literature review and a single case study concerning a lead user research initiative on blood pressure monitoring. The results suggest advantages of executing lead user research in early-stage designing for intelligent ecosystems from the points of view envisioning broad initial ecosystem boundaries, developing first intelligence components, and overcoming research challenges related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…From a design perspective, Kleinsmann et al showed that data-enabled design could support the design process by adding community-level data to the design process (see, e.g., Jung et al, 2022). Through their "Quantified Heart" study, they explored how self-monitoring of blood pressure and other data points (e.g., health-related experiences) of a group of lead users from the Quantified Self community could be a source of new insights and ideas for new health ecosystems (Pannunzio et al, 2020). They found that this new type of user data could support designers in finding the ecosystem boundaries, defining the system and propositions, and getting insights into possible (technical) challenges for users.…”
mentioning
confidence: 99%
“…From a design perspective, Kleinsmann et al showed that data-enabled design could support the design process by adding community-level data to the design process (see, e.g., Jung et al, 2022). Through their "Quantified Heart" study, they explored how self-monitoring of blood pressure and other data points (e.g., health-related experiences) of a group of lead users from the Quantified Self community could be a source of new insights and ideas for new health ecosystems (Pannunzio et al, 2020). They found that this new type of user data could support designers in finding the ecosystem boundaries, defining the system and propositions, and getting insights into possible (technical) challenges for users.…”
mentioning
confidence: 99%